Fluorescence emission behavior of Eu(III) sorbed on calcium silicate hydrates as a secondary mineral formed without drying process - Yuichi NIIBORI (The Japan Society of Mechanical Engineers, 2014)
Calcium silicate hydrate (CSH) is a main component of cement-based material required for constructing the geological repository. As in many countries, since the repository in Japan is constructed below water table, we must consider the interaction of radionuclide with cement materials altered around the repository after the backfill. Using fluorescence emission spectra, so far, the authors have investigated the interaction of Eu(III) (as a chemical analog of Am(III)) with CSH gels as a secondary mineral formed without drying process, considering a condition saturated with groundwater. However, in such fluorescence emission behaviors, a deexcitation process of OH vibrators of light water and a quenching effect caused by Eu-Eu energy transfer between Eu atoms incorporated in the CSH gel must be considered. This study examined the fluorescence emission behavior of Eu(III) sorbed on CSH gels, by using La(III) (non-fluorescent ions) as a diluent of Eu(III). Furthermore, CSH samples were synthesized with CaO, SiO2, and heavy water (D2O) as a solvent in order to avoid the obvious deexcitation process of OH vibrators of light water. In the results, the peak around 618 nm was split into two peaks of 613 nm and 622 nm in the cases of Ca/Si=1.0 and 1.6. Then, the peak of 613 nm decreased with increment of Eu(III)/La(III) ratio. This means that the relative intensity of 613 nm is useful to quantify the amount of Eu(III) incorporated in CSH gel. Besides, the decay behavior of the fluorescence emission did not depend on the Eu/La concentration ratio. That is, such a quenching effect is neglectable. Additionally, the fluorescence emission spectra of Eu(III) showed that the state of Eu(III) depended on Ca/Si ratio of CSH. This suggested that there was several sites in CSH to incorporate Eu(III). When CSH is altered, whole cementitious material in repository must be altered forming cracks and leaching some calcium compositions. Therefore, the adsorptive capacity of CSH might also play a key role to retard the migration of nuclides released from the waste body. This study mentioned the fundamental behaviors on the interaction of radionuclides and the altered CSH around the repository.